Effect of powder composition on the failure and melting behaviour of yttria stabilized zirconia ingot with a bimodal structure. Issue 1 (January 2017) - Oh, Yoon-Suk; Chae, Jung-Min; Choi, Sun-Ah; Han, Yoon-Soo; Kim, Seong-Won; Lee, Sung-Min; Kim, Hyung-Tae; Ahn, Jong-Kee; Kim, Tae-Hyung; Kim, Dong-Hoon
Abstract: Yttria (Y2 O3 ) stabilized zirconia (ZrO2 ) containing 8 wt% yttria, 8YSZ, was fabricated with an ingot shape with different powder compositions. Ingot shape 8YSZ is commercially used as a source to fabricate thermal barrier coatings (TBCs) by an electron beam (EB) evaporation process. Powder mixtures with different mixing ratios using small (mean dia. of ~40 nm) and large (40–80 µm, granulated) raw material powders were used to form the ingots in the present study. In addition, the tetragonal and monoclinic phases of raw powders were used selectively. The ingots from various powder mixtures showed a bimodal structure of small and large grains with 55–60% relative density (3.0–3.5 g/cm 3 ). The ingots formed from the mixtures using nanometer size powder with a large content of the monoclinic phase and several tens of micrometer size powder with the tetragonal phase showed better thermal shock resistance compared to the ingot from a simple mixture with a bimodal particle distribution. Furthermore, for these ingots, it appears that an additional cold isostatic pressing (CIP) process between uni-axial pressing and heat treatment processes might provide mechanical enhancement to form a more stable melt spot during the EB irradiation process compared to other ingot samples.